(untitled) (Revista de Ciências Agroveterinárias, 2019)
The aim of this study was to evaluate the effect of different winter cover plants on soil physical and chemical attributes and corn crop productivity. The experiment was carried out for three crops, from 2011 to 2014. The treatments were winter cover crops vetch, black oat, blue lupin, wild radish, ryegrass and field pea cultivated alone and intercropped with black oat + vetch, black oat + wild radish + vetch, black oat + wild radish, and a control treatment, without the use of cover crops (fallow). The experimental design consisted of random blocks with three repetitions. Chemical and physical soil parameters were evaluated, as well as yield of dry plant biomass of the cover crops and yield of corn cultivated in sucession. The greatest production of dry mass for field pea was obtained in the 2011/2012 crop and for the treatments with black oat + vetch and black oat + wild radish + vetch, in 2012/2013 and 2013/2014. Corn grain yield was higher in the treatments utilizing Fabaceae species and intercropping in the 2011/2012 crop. In the 2012/2013 and 2013/2014 crops, the greatest yield of corn grains was found in the treatments with black oat + vetch + wild radish and blue lupin as cover crops. Growing cover crops for three consecutive years resulted in increase in the organic matter contents and availability of phosphorus and potassium in the soil.